Arts dDucation: research and disobedience - Paiva, José Carlos de (Farol, 2024)
At of imminent ecological and social catastrophe, where humanity is heading for annihilation in the face of the hegemonic power that the West is making global, it is no longer acceptable to view Arts Education, Art and Artistic Teaching as unconcerned about the common future. Establishing as behaviour, the promotion of a performative link to any differentiating activity that moves becomes, imperatively, the path of lucidity that nourishes hope for a new becoming.